Zero-Valent Iron Supported Microbial Reductive Dechlorination of 2,4-Dichlorophenol - Cheng, T.; Dai, Y.Z.; Chen, C.; Q. Huang, Z. (Asian Journal of Chemistry, 2012)
The experiment was conducted to examine the potential of zero-valent iron (Fe0) as the sole electron donor for reductive dechlorination of 2,4-dichlorophenol by mixed culture. The optimal conditions and the sustainability of 2,4-dichlorophenol dechlorination in Fe0+microbe system were also investigated. The results showed that, Fe0 was an effective electron donor to stimulate reductive dechlorination of 2,4-dichlorophenol and 2,4-dichlorophenol (30 mg L-1) could be transformed completely within 68 h. The rate was similar to that with acetate or lactate as electron donor, while the rate was slow with glucose as electron donor. The quantity of Fe0, inoculation added and pH had a significant effect on 2,4-dichlorophenol dechlorination. The optimal quantity of Fe0, inoculation added and initial pH was 2.0 g L-1, 646.4 mg volatile suspended solid L-1 and 8, respectively. Fe0 sustained 2,4-dichlorophenol dechlorination over a long period. 4-Chlorophenol was the intermediate roduct from 2,4-dichlorophenol, but it was difficult to be further degraded.